Investigation of the association between IL-33 levels and the progression of chronic kidney disease (CKD) - Israa Jafar (Journal of Health and Biology, 2026)
Background: Chronic Kidney Disease (CKD) is a progressive loss of kidney function. Interleukin-33 (IL-33) is a potential marker of inflammation associated with CKD. This study analyzed the association between IL-33 levels and the progression of kidney disease to examine whether it could be used as a biomarker of disease severity in CKD. Methods: In this cross-sectional study, 200 participants (80 healthy, 120 patients with CKD at different stages) were included. IL-33 was quantified in plasma by ELISA. Glomerular filtration rate (GFR), serum creatinine, and albuminuria were assessed. The ability to diagnose was evaluated with correlation analysis and receiver operating characteristic (ROC) curves. Results: IL-33 levels were significantly higher in CKD patients (Stage 4-5: 52.1 ± 12.3 pg/mL) than controls (14.3 ± 5.2 pg/mL, p < 0.001). IL-33 correlated strongly negatively with GFR (r = -0.72, p < 0.001), and positively with serum creatinine (r = 0.68, p < 0.001) and albuminuria (r = 0.64, p < 0.001). The area under the ROC curve (AUC) was 0.87, indicating that the classification of the early and advanced CKD stages has good predictive value. Conclusion: Elevated IL-33 has been strongly associated with the progression of CKD, and therefore it could be used as a new marker of disease severity. It is advised that further research be carried out to explore its therapeutic potential.